YOUNG ADULTS’ AWARENESS, KNOWLEDGE, AND USE OF LOCAL LANGUAGE BETAWI – ORA IN BEKASI - Yuki Priliani Putri; Wiwik Retno Handayani (IKIP Siliwangi, 2023)
Language does not only play a role as a communication tool, but also as cultural identification. This paper aims to discover young adults' awareness of the local language in Bekasi, to find out the existence of the local language 'Betawi-Ora' in Bekasi, and its application of it in daily life. The writer applied the quantitative method to collect and analyze the data. The data were collected by online questionnaire and interview with 31 young adults from Bekasi in the range of age 16 – 26 and 27 – 38. The survey contained 27 questions which dived into 5 questions for the awareness aspect, 15 questions for the knowledge aspect, and 7 questions for the usage aspect. Moreover, the interview was represented by 4 young adults who were born in Bekasi. The result of the survey showed that plenty of them are aware of the local language and culture in Bekasi. More than half of them know that the local language is called 'Betawi-Ora' and its words, but only unfamiliar words they did not recognize them. They preferred to apply the local language frequently only to their close friends in Bekasi to strengthen their relationships. Keywords: Awareness; Local Language; Usage